2020
DOI: 10.3390/ani10122448
|View full text |Cite
|
Sign up to set email alerts
|

The LEPR Gene Is Associated with Reproductive Seasonality Traits in Rasa Aragonesa Sheep

Abstract: The aim of this study was to characterize and identify causative polymorphisms in the leptin receptor (LEPR) gene responsible for the seasonal variation of reproductive traits in sheep. Three reproductive seasonality traits were studied: the total days of anoestrous (TDA), the progesterone cycling months (P4CM) and the oestrous cycling months (OCM). In total, 18 SNPs were detected in 33 ewes with extreme values for TDA and OCM. Six SNPs were non-synonymous substitutions and two of them were predicted in silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…In our work, LEPR was identified as a candidate gene for the pregnancy rate. This gene has already been associated with several reproduction traits, including pregnancy [67][68][69][70]. The genes GHR and LPAR2 are associated with sheep reproduction [71,72], while DMXL1 is related to reproduction traits in heifers [73].…”
Section: Discussionmentioning
confidence: 99%
“…In our work, LEPR was identified as a candidate gene for the pregnancy rate. This gene has already been associated with several reproduction traits, including pregnancy [67][68][69][70]. The genes GHR and LPAR2 are associated with sheep reproduction [71,72], while DMXL1 is related to reproduction traits in heifers [73].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we discovered a relationship between the LEPR gene and such growth parameters as BW56, DCW, BrW, TW, and ADBWG. It should also be noted that a fairly large number of other studies have demonstrated the LEPR gene effects on growth, productivity, and reproduction in various farm animals [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ], including poultry [ 78 , 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genes, as an integral part of this process, are fundamentally responsible for the regulation of traits. Single trait is intricately regulated by multiple microeffective genes; thus, human exploration of genes has never ceased, and there are numerous studies on reproductive traits [1][2][3][4]. In animal husbandry, elucidating the effects of genes on reproductive traits is important to improve the economic efficiency of breeding.…”
Section: Introductionmentioning
confidence: 99%